Mexican multinationals and the Sustainable Development Goals: The case of CEMEX and BIMBO - Pérez-Solorzano, Jesús Manuel (2024)
The objective of this research is to be able to identify which SDGs have been addressed by the main Mexican multinational companies. To achieve this objective, the sustainability reports of 2016, 2017, 2018, 2019, 2020, 2021 and 2022 of the Mexican multinationals BIMBO and CEMEX will be analyzed. To carry out this analysis, the qualitative research software ATLAS.ti was used. The results indicate that companies are not exempt from obtaining economic benefits and the SDGs that are most addressed are 3 "Health and Well-being" and 6 "Water and Sanitation". The general conclusion indicates that SDG 3 Health and well-being is of the utmost importance for BIMBO and CEMEX.